RISK MANAGEMENT AND RESPONSE MEASURES FOR BIDDING AND TENDERING IN CONSTRUCTION PROJECTS (World Science, 2023)
Bidding is a necessary procedure for the implementation of construction projects, but also an important link in the preliminary stage of construction projects, it is not only the core procedure to control the schedule, quality and cost, but also a necessary means for the procedural management of construction projects. Therefore, this paper analyses the risk of bidding for construction projects through the Gantt chart method, bidding method, and puts forward the corresponding risk management measures, the first part of the potential risk of bidding analysis, the second part of the risk management in the project bidding through the three parts of the business, internal, and supervision of risk management research, and the third part of the risk management of the measures to cope with the risk management, I hope that this paper's research can give the help related to construction project bidding.